2019
DOI: 10.1111/cen3.12550
|View full text |Cite
|
Sign up to set email alerts
|

Reduced perforin release from T cells as a mechanism underlying hypothermia‐mediated neuroprotection

Abstract: Objective The underlying mechanisms of therapeutic hypothermia, which protects neurons after severe brain damage, are partially understood. T cells infiltrate the brain within days after cerebral ischemia and play essential roles in exacerbating the delayed phase of brain injury by producing cytotoxic factors, which were also systematically shown to be involved in brain damage. Periphery brain abnormalities are interesting, because the periphery might constitute a pathway to the central nervous system and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Indeed, the immune profile of patients with severe COVID-19 admitted to intensive care compared to non-intensive care patients demonstrates significantly reduced perforin expression [ 12 ]. In vitro studies using incubated human lymphocytes found that compared to normal body temperature (37°C), perforin expression by CD4 + and CD8 + T cells was significantly reduced at temperatures of 33°C by over 50% and 35%, respectively, but, interestingly, raised at the modestly higher temperature of 39°C [ 13 ]. Similar in vitro effects of temperature have been described for the expression of Fas ligand [ 14 ].…”
mentioning
confidence: 99%
“…Indeed, the immune profile of patients with severe COVID-19 admitted to intensive care compared to non-intensive care patients demonstrates significantly reduced perforin expression [ 12 ]. In vitro studies using incubated human lymphocytes found that compared to normal body temperature (37°C), perforin expression by CD4 + and CD8 + T cells was significantly reduced at temperatures of 33°C by over 50% and 35%, respectively, but, interestingly, raised at the modestly higher temperature of 39°C [ 13 ]. Similar in vitro effects of temperature have been described for the expression of Fas ligand [ 14 ].…”
mentioning
confidence: 99%